2023
DOI: 10.1111/cas.15783
|View full text |Cite
|
Sign up to set email alerts
|

In vivo CRISPR screens identify RhoV as a pro‐metastasis factor of triple‐negative breast cancer

Abstract: Metastasis is the main death reason for triple-negative breast cancer (TNBC). Thus, identifying the driver genes associated with metastasis of TNBC is urgently needed.CRISPR screens have dramatically enhanced genome editing and made it possible to identify genes associated with metastasis. In this study, we identified and explored the crucial role of ras homolog family member V (RhoV) in TNBC metastasis. Here, we performed customized in vivo CRISPR screens targeting metastasis-related genes obtained from trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In cancer cells (LoVo and SW480), knockout of Aldolase B using CRISPR demonstrated that Aldolase B inhibits proliferation, migration, and invasion in these cancer cells ( Li et al, 2017 ). RhoV is a key driver gene associated with and is upregulated in triple-negative breast cancer ( Jin et al, 2023 ). Studies have shown in vivo functional screens identified RhoV as a regulator of tumor metastasis ( Jin et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In cancer cells (LoVo and SW480), knockout of Aldolase B using CRISPR demonstrated that Aldolase B inhibits proliferation, migration, and invasion in these cancer cells ( Li et al, 2017 ). RhoV is a key driver gene associated with and is upregulated in triple-negative breast cancer ( Jin et al, 2023 ). Studies have shown in vivo functional screens identified RhoV as a regulator of tumor metastasis ( Jin et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
“…RhoV is a key driver gene associated with and is upregulated in triple-negative breast cancer ( Jin et al, 2023 ). Studies have shown in vivo functional screens identified RhoV as a regulator of tumor metastasis ( Jin et al, 2023 ). Jin et al have demonstrated that the knockout of RhoV suppressed cell invasion, migration, and metastasis ( Jin et al, 2023 ).…”
Section: Applications Of Crispr/cas9 In Cancer Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…RhoUV proteins have also been linked to growth factor receptor tyrosine kinase signaling, primarily through the N-terminal SH3-binding domain. In breast cancer cells, RhoV was shown to directly bind to Grb2, an SH3 domain-containing adapter protein that functions downstream of the epidermal growth factor receptor (EGFR) [ 34 ]. Disrupting the binding between RhoV and Grb2 inhibited EGF-dependent migration.…”
Section: Introductionmentioning
confidence: 99%